Interpretations of the Northern Ireland problem - appraisal - Whyte, John (Economic & Social Studies, 1978)
The most useful contribution to be made at this point, then, seems to lie not in adding to the innumerable theories in the field, but rather in assessing those theories already proposed. This paper is an attempt to fulfil that purpose. It will not be a synthesis: the divergence between theories is still too great for a synthesis to be practicable. On the other hand, it will be more than a mere inventory, in which all theories are listed as if of equal merit: for even if one cannot make a final choice between current interpretations, some are clearly more satisfactory than others. Rather, it will be an appraisal, in which the more promising interpretations are distinguished from the less adequate ones, and in which an indication is given of the work still to be done if a synthesis is to emerge in the future. For convenience of arrangement, the interpretations will be considered under two headings: first, theories of Marxist provenance, and then, the much more heterogeneous collection of theories whose inspiration comes from other than Marxist sources.
Keywords: Politics and government - Northern Ireland; Conflict - Northern Ireland